Developmentally regulated expression of a chicken muscle-specific gene in stably transfected rat myogenic cells. - Nudel, U (1985)
To test the evolutionary conservation of DNA sequences specifying the developmentally regulated expression of the skeletal muscle actin gene, a recombinant plasmid containing the chicken skeletal muscle actin gene was introduced into rat myogenic cells. In a significant number of isolated clones, the accumulation of chicken actin mRNA increased greatly during differentiation. To test the expression in myogenic cells of a gene that is normally expressed during terminal differentiation of another tissue, rat myogenic cells were transfected with a mouse/human beta-globin chimeric gene. A decrease by a factor of 2-3 in the amount of globin mRNA during differentiation was observed in most clones in which the gene was expressed. The results indicate the conservation of the muscle-specific regulatory DNA sequences for more than 300 Myr.